Effect of problem-based learning on students’ problem-solving ability to learn physics - Gumisirizah, Nicholus; MMuwonge, Charles; Nzabahimana, Joseph (Physics Education, 2023)
A learner’s success is supported by the ability to understand real-world problems. This study aimed to examine the effect of problem-based learning on problem-solving ability in the teaching and learning of physics. The study was guided by socio-constructivism theory. A quasi-experiment was conducted with 829 Senior-2 Physics students (age 13–15) from eight (8) selected lower secondary schools in Sheema District, Uganda. Schools were assigned to treatment and control groups using a purposive random sampling technique. Students’ problem-solving ability was measured by conducting a problem-solvingabilitytestineachgroupbeforeandafterstudyingachapter on simple machines in physics. Repeated measures analysis of variances was applied for data analysis. The study’s findings showed a significant improvement in students’ problem-solving ability with simple machines in the treatment group compared to the control group (p < .001). Therefore, educators are encouraged to embrace learner-centred methods that enhance students’ problem-solving abilities to help them compete in the world of work.
Keywords: Problem-based learning; Problem-solving ability; Simple machine; Ugandan secondary school